2021
DOI: 10.1111/jcv2.12002
|View full text |Cite
|
Sign up to set email alerts
|

Field of daydreams? Integrating mind wandering in the study of sluggish cognitive tempo and ADHD

Abstract: In this editorial perspective, we consider the potential conceptual and empirical overlap between the research on mind wandering, particularly in its pathological extreme, and that on sluggish cognitive tempo (SCT) as it has diverged from research on attention-deficit/hyperactivity disorder. The more advanced state of research findings on the nature and correlates of mind wandering relative to that of SCT is used to suggest a variety of avenues of investigation into SCT, such as its phenomenology, positive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…A majority of parents also indicated that they viewed their child’s SCT behaviors to be a strength to at least some degree. Consistent with cognitive science studies of mind wandering (Becker & Barkley, 2021; Smallwood & Schooler, 2015), parents indicated that their child’s propensity to daydream facilitated creativity and imagination. As a result, several parents linked their child’s creativity and imagination with strong abilities in the visual and performance arts.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…A majority of parents also indicated that they viewed their child’s SCT behaviors to be a strength to at least some degree. Consistent with cognitive science studies of mind wandering (Becker & Barkley, 2021; Smallwood & Schooler, 2015), parents indicated that their child’s propensity to daydream facilitated creativity and imagination. As a result, several parents linked their child’s creativity and imagination with strong abilities in the visual and performance arts.…”
Section: Discussionmentioning
confidence: 55%
“…Do children with SCT describe their daydreams in terms of being involuntary or under their control, about real life or imaginary situations, or about the past or the future? Answers to these questions are entirely unknown despite their importance for more fully understanding the SCT construct from the perspectives of the individuals whose lives it directly impacts, which in turn will have implications for theory and intervention (Becker & Barkley, 2021).…”
Section: Phenomenology Of Sctmentioning
confidence: 99%
“…Given the fact that results suggest that the performance on the SSAIS-R subtests did not differ significantly between the ADHD and SCT groups we draw one of two conclusions. It could be that ADHD and SCT are not two distinct disorders as suggested by Becker and Barkley (2021) or that the two groups perform similarly on a cognitive assessment such as the SSAIS-R.…”
Section: Discussionmentioning
confidence: 99%
“…SCT: daydreaming, hypo-arousal, confusion, objectively inattentive, lethargy, slow psychomotor speed, difficulty in following instructions, drowsiness, apathy, internally distracted, slow task completion, lack of initiative and decline in sustained performance (Barkley, 2018). The main difference between these two disorders seems to be that ADHD is characterised by external distractibility whereas SCT seems to be characterised by internal distractibility (Becker & Barkley, 2021). Furthermore, impulsivity is one of the core categories of symptoms in ADHD but is not a distinct symptom or cluster of symptoms of SCT (Barkley, 2005).…”
mentioning
confidence: 99%
“…The inhibitory difficulties associated with both disorders do not only seem to differ from each other in their intensity, but also in their modality. While the inhibitory regulation difficulties in ADHD appear to be behavioural in nature, leading to its distinctive hyperactivity [60,61], those in SCT appear to be cognitive in nature, leading to its sufferers' particular tendency to daydream, ruminate and let their mind wonder [62,63].…”
Section: Introductionmentioning
confidence: 99%